2021
DOI: 10.5194/hess-25-5623-2021
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation greening weakened the capacity of water supply to China's South-to-North Water Diversion Project

Abstract: Abstract. Recent climate change and vegetation greening have important implications for global terrestrial hydrological cycles and other ecosystem functions, raising concerns about the watershed water supply capacity for large water diversion projects. To address this emerging concern, we built a hybrid model based on the Coupled Carbon and Water (CCW) and Water Supply Stress Index (WaSSI) models and conducted a case study on the upper Han River basin (UHRB) in Central China that serves as the water source are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 91 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…on paired-catchment experiments, and is still used today (Van Loon et al, 2019). However, separating the effects of vegetation change and climate variability on runoff remains a great challenge due to the complex interactions between climate variability and vegetation change (Cavalcante et al, 2019;Jones et al, 2006;Zhang et al, 2021). Moreover, persistent hydroclimatic non-stationary changes observed during the past few decades have increased both temperatures and occurrences of extreme weather events (such as multiyear drought).…”
Section: Introductionmentioning
confidence: 99%
“…on paired-catchment experiments, and is still used today (Van Loon et al, 2019). However, separating the effects of vegetation change and climate variability on runoff remains a great challenge due to the complex interactions between climate variability and vegetation change (Cavalcante et al, 2019;Jones et al, 2006;Zhang et al, 2021). Moreover, persistent hydroclimatic non-stationary changes observed during the past few decades have increased both temperatures and occurrences of extreme weather events (such as multiyear drought).…”
Section: Introductionmentioning
confidence: 99%
“…The other group suggests that forests retain more water through their deep root system via increasing soil water storage (Li et al., 2018; Ward et al., 2021; Yao et al., 2016; W. Zhang et al., 2016; Zhou et al., 2010). Observations support both groups to some extent, indicating that a more detailed exploration of the hydrological response to afforestation is required (Ward et al., 2021; Xiao et al., 2020; J. Zhang et al., 2021; Zhao et al., 2021; Zhou et al., 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Generally, there are two groups of studies with contrasting conclusions on the effects of afforestation on runoff. One group argues that afforestation has a negative effect on a basin’s water yield mainly owing to an enhanced E (Andréassian, 2004; Brown et al., 2005; Feng et al., 2016; Swank & Douglass, 1974; Xiao et al., 2020; M. Zhang et al., 2021; Zhao et al., 2021). The other group suggests that forests retain more water through their deep root system via increasing soil water storage (Li et al., 2018; Ward et al., 2021; Yao et al., 2016; W. Zhang et al., 2016; Zhou et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was found that vegetation cover can weaken the water supply capacity of the South-North Water Transfer to some extent. For example, Zhang et al [66] found that vegetation greening may exacerbate the degree of hydrological aridity. The increase in forest cover can reduce runoff in the HRB by as much as 0.19%, thus affecting river health to some extent [63].…”
Section: Lucc Change Impacts On Watershed Water Resourcesmentioning
confidence: 99%